"Tempus Divitiae": Locomotion orientation and evaluation of time as a precious resource. (August 2019) - Amato, Clara; Baldner, Conrad S; Pierro, Antonio; Kruglanski, Arie W
Prior research on time issues has demonstrated that the value of time is subjective and shows that different evaluations of time (as a valuable or as an undefined resource) correspond to different attitudes, behaviors, and emotions. Based on recent research on the relationship between time and motion, the present research aimed to investigate the relationship between locomotion orientation (i.e., proclivity toward movement and change) and the evaluation of time as a resource. Two studies were conducted with 313 (244 students and 69 workers) and 139 (students) Italian participants, respectively. In the first study, The Locomotion Regulatory Mode Scale and the Mental Account Scale (Time version) were administered, while in the second study, participants were presented with two scenarios of a transaction where prior investments of time led to negative outcomes. The results of the two studies confirmed the hypotheses that (1) locomotion orientation is associated with the existence of a mental accounting process for time investments and (2) locomotion orientation is associated with greater disappointment from negative consequences of poor time expenditures. Theoretical and practical implications are discussed.